Utilizing blockchain technology to enhance Halal integrity: The perspectives of Halal certification bodies - Tieman, Marco; Mohd Ridzuan, Darun; Fernando, Yudi; Abu Bakar, Ngah (Springer Nature Switzerland, 2019)
Brand owners face multiple challenges in establishing end-to-end halal supply chains and in halal issue management. To this end, leading Halal Certification Bodies (HCBs) set up a discussion group to achieve consensus on a way forward and to examine the potential role of the halal blockchain in resolving these issues, as well as the key parameters, and segregation and communication requirements of the blockchain. Halal issues can be divided broadly into three areas: contamination, non-compliance and perception. Only cases involving contamination and non-compliance need to be reported to the HCB. Consensus has been achieved in the segregation of halal supply chains in terms of designated halal transport, storage and halal compliant terminals, for Muslim (majority) countries, whereas in non-Muslim (majority) countries greater leniency is possible. Effective segregation is only possible with effective communication, whereby the term ‘halal supply chain’ is encoded in freight documents, on freight labels and within the ICT system.